2008
DOI: 10.1128/mcb.00394-08
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty2-Mediated Inhibition of Fibroblast Growth Factor Signaling Is Modulated by the Protein Kinase DYRK1A

Abstract: Raf-MEK-extracellular signal-regulated kinase (Erk) signaling initiated by growth factor-engaged receptor tyrosine kinases (RTKs) is modulated by an intricate network of positive and negative feedback loops which determine the specificity and spatiotemporal characteristics of the intracellular signal. Well-known antagonists of RTK signaling are the Sprouty proteins. The activity of Sprouty proteins is modulated by phosphorylation. However, little is known about the kinases responsible for these posttranslation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 51 publications
(61 reference statements)
5
64
0
1
Order By: Relevance
“…Similarly, deletion of the receptor tyrosine kinase Met, the ligand of which is hepatocyte growth factor (HGF), also restricted branching morphogenesis, kidney size and nephron number (Ishibe et al, 2009). These results also raise the possibility that inhibitors of Ret signaling can inhibit other tyrosine kinases important for branching morphogenesis; for example, the Sprouty1 protein is known to suppress Fgfr signaling (Aranda et al, 2008). This further increases the complexity of signaling in the ureteric bud epithelium and makes interpretations at the biochemical level difficult.…”
Section: The Ureteric Budmentioning
confidence: 92%
“…Similarly, deletion of the receptor tyrosine kinase Met, the ligand of which is hepatocyte growth factor (HGF), also restricted branching morphogenesis, kidney size and nephron number (Ishibe et al, 2009). These results also raise the possibility that inhibitors of Ret signaling can inhibit other tyrosine kinases important for branching morphogenesis; for example, the Sprouty1 protein is known to suppress Fgfr signaling (Aranda et al, 2008). This further increases the complexity of signaling in the ureteric bud epithelium and makes interpretations at the biochemical level difficult.…”
Section: The Ureteric Budmentioning
confidence: 92%
“…Dissociated cells were plated in the absence of the drug, and the number of secondary spheres formed was counted. ***P ≤ 0.001. dampens its inhibitory influence on FGF-induced MAPK activation (57). This phosphorylation could potentially regulate SPRY2 binding to regulatory proteins and help discriminate between the EGF and FGF signaling pathways, as described for other residues (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…Spry2 has been reported to interact with at least two other kinases, namely Tesk1 and DYRK1A (13,14). Although the interaction with these two kinases abrogated the capacity of Spry2 to inhibit ERK1/2 activation, the reverse was true with the Spry2-PKC␦ interaction, with Spry2 curtailing the contribution of PKC␦ to ERK1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 76%
“…To date, a number of interacting partners of Spry have been identified, including c-Cbl, Grb2, Tesk1, Raf1, PP2A, and DYRK1A (11)(12)(13)(14)(15); several of these interactions contribute to the function of Spry2 as an inhibitor of the Ras/ERK pathway. In addition to binding to other proteins, studies have shown that Spry2 can affect the signaling effect of certain proteins, such as protein kinase C ␦ (PKC␦).…”
mentioning
confidence: 99%